2005
DOI: 10.1529/biophysj.104.050559
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Lateral Mobility Obstructed by Polymer-Tethered Lipids Studied at the Single Molecule Level

Abstract: Obstructed long-range lateral diffusion of phospholipids (TRITC-DHPE) and membrane proteins (bacteriorhodopsin) in a planar polymer-tethered 1-stearoyl-2-oleoyl-sn-glycero-3-phosphocholine bilayer is studied using wide-field single molecule fluorescence microscopy. The obstacles are well-controlled concentrations of hydrophobic lipid-mimicking dioctadecylamine moieties in the polymer-exposed monolayer of the model membrane. Diffusion of both types of tracer molecules is well described by a percolating system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
194
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(212 citation statements)
references
References 72 publications
(105 reference statements)
17
194
1
Order By: Relevance
“…These data compare well with previous reports, where diffusion constants were even correlated with height and mole percentage of tethers. 40,41 Some have also measured diffusion constants of tethered bilayers and of bilayers supported directly on silicon and have shown that comparable high diffusion constants have been obtained in both cases. 17 The somewhat higher absolute values of the diffusion constants measured here, i.e., a minor difference of ϳ2 versus ϳ1 m 2 / s, could be inherent to the different analyzing techniques.…”
Section: Fluorescence Imaging Of Tethered Lipid Membranesmentioning
confidence: 96%
“…These data compare well with previous reports, where diffusion constants were even correlated with height and mole percentage of tethers. 40,41 Some have also measured diffusion constants of tethered bilayers and of bilayers supported directly on silicon and have shown that comparable high diffusion constants have been obtained in both cases. 17 The somewhat higher absolute values of the diffusion constants measured here, i.e., a minor difference of ϳ2 versus ϳ1 m 2 / s, could be inherent to the different analyzing techniques.…”
Section: Fluorescence Imaging Of Tethered Lipid Membranesmentioning
confidence: 96%
“…Equally critical will be the direct measurements of half-lives in adhesive interfaces. Two approaches that are currently tractable are the use of supported planar bilayers to visualize interactions (20) and erythrocyte-based interaction sensors (17), but moving these measurements into native cell-cell interfaces would also be an important challenge for the future.…”
Section: Future Prospectsmentioning
confidence: 99%
“…[15][16][17] The lipid diffusion coefficients calculated using the BPE method are very similar to previously reported values obtained using other methods, such as flash bleaching and single molecule measurements. 18 The diffusion coefficients measured for the peptides, however, were very low. We therefore explored whether the incorporation of a PEG cushion between the bilayer and the substrate increases protein mobility.…”
Section: ͑2͒mentioning
confidence: 96%